2019
DOI: 10.1002/chem.201900266
|View full text |Cite
|
Sign up to set email alerts
|

Weak Pnictogen Bond with Bismuth: Experimental Evidence Based on Bi−P Through‐Space Coupling

Abstract: To study pnictogen bonding involving bismuth, flexible accordion‐like molecular complexes of the composition [P(C 6 H 4 ‐ o ‐CH 2 SCH 3 ) 3 BiX 3 ], (X=Cl, Br, I) have been synthesised and characterised. The strength of the weak and mainly electrostatic interaction between the Bi and P centres strongly depends on the character of the halogen substituen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 72 publications
3
47
0
Order By: Relevance
“…The central Sb atom of SbCl 3 engages in three Sb···O contacts short enough to be characterized as ZBs 92 or in three Sb···S bonds with trithiane; 93 three Bi···S bonds with BiX 3 have also been observed quite recently. 94 Radha et al 95 have shown that a Sb atom can engage in three Sb···S ZBs, that complement its three covalent Sb–S bonds. Their analysis also concluded that a bulky alkyl substituent can inhibit the formation of this number of noncovalent interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The central Sb atom of SbCl 3 engages in three Sb···O contacts short enough to be characterized as ZBs 92 or in three Sb···S bonds with trithiane; 93 three Bi···S bonds with BiX 3 have also been observed quite recently. 94 Radha et al 95 have shown that a Sb atom can engage in three Sb···S ZBs, that complement its three covalent Sb–S bonds. Their analysis also concluded that a bulky alkyl substituent can inhibit the formation of this number of noncovalent interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In the following we only discuss the results obtained at the ωB97XD/(aug-)cc-pVDZ(-PP) level, which has been used successfully for similar systems before. 56 The solvent effects were simulated using the polarizable continuum model (PCM) with dichloromethane as solvent.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Altogether, the phosphorus and the three sulfur donor atoms endow the PS 3 ligand with versatile coordination ability, complementing the previously reported tridentate and tetradentate coordination modes. 56 The UV–vis absorption bands connected to excitations from the dibismuthate core into the π* system of the phosphonium units can be tuned by varying the halogen substitutions at the bismuth centers in the bis-zwitterions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of these ligands possess Ndonors, [2][3][4][5][6][7][8] whereas as P-donors are only occasionally encountered. [9][10][11][12][13][14][15] As part of our research programme on peri-substituted scaffolds, we recently prepared the monoarylbismuth dichloride RBiCl 2 (1a, R = 6-diphenylphosphinoacenaphth-5-yl), the analogous arylantimony dichloride RSbCl 2 (1b) 16 as well as the diarylantimony chloride R 2 SbCl (2b) and the triarylantimony R 3 Sb (3b). 17 The latter two compounds were also used as (coordination noninnocent) ligands towards late transitions metals.…”
Section: Introduction *mentioning
confidence: 99%